2006
DOI: 10.1053/j.gastro.2006.02.057
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Human Micro-RNA in Growth and Response to Chemotherapy in Human Cholangiocarcinoma Cell Lines

Abstract: Alterations in miRNA expression contribute to tumor growth and response to chemotherapy. Aberrantly expressed miRNA or their targets will provide mechanistic insight and therapeutic targets for cholangiocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
747
1
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 883 publications
(784 citation statements)
references
References 38 publications
31
747
1
5
Order By: Relevance
“…The expression of miR-370, miR-222, miR-200c, miR-181c, miR-27a and miR-148a were further analyzed in a total of 33 GC and NCM pairs from the group 1 patients (Table 1) to confirm the changes in expression level in the tumor tissue (Meng et al, 2006(Meng et al, , 2008Liu et al, 2007;Ladeiro et al, 2008;Lujambio et al, 2008). miR-370 was found to be generally overexpressed in GC, with a mean DDCt of 1.45 (Figure 2a).…”
Section: Mir-370 Overexpression In Gcmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of miR-370, miR-222, miR-200c, miR-181c, miR-27a and miR-148a were further analyzed in a total of 33 GC and NCM pairs from the group 1 patients (Table 1) to confirm the changes in expression level in the tumor tissue (Meng et al, 2006(Meng et al, , 2008Liu et al, 2007;Ladeiro et al, 2008;Lujambio et al, 2008). miR-370 was found to be generally overexpressed in GC, with a mean DDCt of 1.45 (Figure 2a).…”
Section: Mir-370 Overexpression In Gcmentioning
confidence: 99%
“…For instance, miR-21 has been shown to be overexpressed in a variety of cancers and targets phosphatase and tensin homolog (PTEN), reversion-inducingcysteine-rich protein with kazal motifs (RECK), programmed cell death and four other genes as well as tropomyosin-1 (Meng et al, 2006;Si et al, 2007;Zhu et al, 2007;Lu et al, 2008;Zhang et al, 2008). In contrast, let-7 is a tumor-suppressive miRNA family and is underexpressed in various tumors; it targets Ras, HMGA2 and others genes (Johnson et al, 2005;Yanaihara et al, 2006;Motoyama et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For example, overexpression of miR-21 (identified as HRM), enhances the effect of gemcitabine on cholangiocarcinoma cells. 39 …”
Section: Towards Future Applications In Clinical Oncologymentioning
confidence: 99%
“…We have also shown recently that the exogenous addition of miR-34 protects breast cancer cells from radiation-induced cell death and that lowering the level of miR-34a with anti-miR radiosensitized the cells (Kato et al, 2009). Significantly, works by Meng et al (2006) and Weidhaas et al (2007) also showed that chemotherapy and radiation treatment alter miRNA expression, perhaps as part of the cellular damage repair pathway. As the development of chemotherapy-and radiotherapy-resistant cancer cells accounts for the majority of treatment failure and recurrence, it would be interesting to profile the miRNA differences between the resistant and sensitive populations to identify miRNAs that are involved in the resistant mechanism or pathways, which can then be used to resensitize tumors to available treatments.…”
Section: Mirnas As Therapeuticsmentioning
confidence: 84%
“…Meng et al (2006) reported the use of anti-miR-21 and anti-miR-200b AMOs to increase the susceptibility of colangiocarcinoma cells to the chemotherapy drug gemcitabine. MiR-200c levels were reported to be high in well-differentiated endometrial, breast and ovarian cancer cell lines, but extremely low in poorly differentiated cancer cells and restoration of miR-200c in these cells increases their sensitivity to microtubule-targeting agents by 85% (Cochrane et al, 2009).…”
Section: Mirnas As Therapeuticsmentioning
confidence: 99%